BUILDING A SPIRITUAL WORK CULTURE BY READING THE QUR'AN BEFORE PATI ISLAMIC HOSPITAL HANDOVER AT THE NURSE STATION - Sofiati; Feri Catur Yuliani; Yeni Rusyani; Akbar Amin Abdullah (RADJA PUBLIKA, 2025)
This study discusses the application of recitation therapy as an effective mental health healing method to reduce stress and anxiety and strengthen spiritual connection with Allah SWT. However, at the Pati Islamic Hospital, recitation is not recommended. This Qur'an has not yet become a routine habit, so there needs to be systematic implementation so that this therapy can improve the emotional well-being of health workers. Building an Islamic work culture by starting activities by remembering Allah SWT, instilling a sense of discipline and sincerity, and regularly reciting holy verses to create a harmonious work atmosphere and also improve work ethic. Qualitative action research approach with the following stages: problem identification, implementation observation, and impact evaluation through interviews and reflection with health workers. Tilawah therapy has a positive impact on the emotional and spiritual well-being of health workers, creates a calm working atmosphere, strengthens Islamic work culture (sincerity, responsibility, empathy), reduces stress, increases focus, strengthens relationships between staff, and supports humanistic and quality health services. The implementation of tilawah therapy at the RSI Pati Nurse Station effectively improves emotional balance, mental calm, work ethic, and the quality of healthcare services. This therapy also fosters a harmonious, religious, and spiritual Islamic work culture, creating a humanistic and meaningful work environment.